Metabolic changes in summer active and anuric hibernating free-ranging brown bears (Ursus arctos). - Peter Stenvinkel (Public Library of Science (PLoS), 2013)
The brown bear (Ursus arctos) hibernates for 5 to 6 months each winter and during this time ingests no food or water and remains anuric and inactive. Despite these extreme conditions, bears do not develop azotemia and preserve their muscle and bone strength. To date most renal studies have been limited to small numbers of bears, often in captive environments. Sixteen free-ranging bears were darted and had blood drawn both during hibernation in winter and summer. Samples were collected for measurement of creatinine and urea, markers of inflammation, the calcium-phosphate axis, and nutritional parameters including amino acids. In winter the bear serum creatinine increased 2.5 fold despite a 2-fold decrease in urea, indicating a remarkable ability to recycle urea nitrogen during hibernation. During hibernation serum calcium remained constant despite a decrease in serum phosphate and a rise in FGF23 levels. Despite prolonged inactivity and reduced renal function, inflammation does not ensue and bears seem to have enhanced antioxidant defense mechanisms during hibernation. Nutrition parameters showed high fat stores, preserved amino acids and mild hyperglycemia during hibernation. While total, essential, non-essential and branched chain amino acids concentrations do not change during hibernation anorexia, changes in individual amino acids ornithine, citrulline and arginine indicate an active, although reduced urea cycle and nitrogen recycling to proteins. Serum uric acid and serum fructose levels were elevated in summer and changes between seasons were positively correlated. Further studies to understand how bears can prevent the development of uremia despite minimal renal function during hibernation could provide new therapeutic avenues for the treatment of human kidney disease.